DOKTRIN WIRAUSAHA ALA RASÛLULLÂH - Farid Firmansyah (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2009)
Indonesia face the challenge of economy globalization era that isfree trade system that has been agreed by the world. Tradesystem and free-opened investment becomes globalcommitment signed by agreement of GATT (General Agreementon Tariffs and Trade) and the form of world trade organization,WTO. Indonesia must be able to prepare human resource to facethis global challenge. Indonesian government needs younggeneration that has competitive advantage. It means that theyare ready to do business by following the model of a truebusinessman figure, our prophet Muhammad saw. It is hopedthat young Indonesians can develop the Indonesian economy byapplying business management that had been applied by theprophet Muhammad saw. It has been proved that hismanagement principle that he did was accurate and reliable thatmade his business form always get profit and never loss.